2007
DOI: 10.1073/pnas.0611515104
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of the zebra finch brain during song stimulation suggests a lateralized response topography

Abstract: Electrophysiological and activity-dependent gene expression studies of birdsong have contributed to the understanding of the neural representation of natural sounds. However, we have limited knowledge about the overall spatial topography of song representation in the avian brain. Here, we adapt the noninvasive functional MRI method in mildly sedated zebra finches (Taeniopygia guttata) to localize and characterize song driven brain activation. Based on the blood oxygenation level-dependent signal, we observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
55
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 62 publications
12
55
0
1
Order By: Relevance
“…Our observation of stronger absolute responses in the right hemisphere is consistent with the finding in a recent fMRI study that BOLD responses to auditory stimuli were larger in the right hemisphere than in the left (25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observation of stronger absolute responses in the right hemisphere is consistent with the finding in a recent fMRI study that BOLD responses to auditory stimuli were larger in the right hemisphere than in the left (25).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our results demonstrate lateralized acoustic processing in songbird NCM, adding to various reports of lateral differences observed in adult songbirds based on lesion and behavioral observations (19)(20)(21), electrophysiological recording (22,23), immediate early gene induction (24), and fMRI (25,26). Our observation of stronger absolute responses in the right hemisphere is consistent with the finding in a recent fMRI study that BOLD responses to auditory stimuli were larger in the right hemisphere than in the left (25).…”
Section: Discussionsupporting
confidence: 92%
“…The current NMR technology with strong magnets (7T and 9T) now makes it possible to obtain spatial resolutions that are accurate enough to study a brain as small as that of the songbird (74). Even 3T magnets are sufficient to detect how early social and song-learning experience affects patterns of song-specific auditory responses (75). An example of this approach is a recent study that used brain imaging to test how vocal and auditory experience and social environment shape auditory responses (76).…”
Section: Combining Behavioral Studies Of Song Development With Neuralmentioning
confidence: 99%
“…But some type of animal research may entail the same semantic problems as human studies with speech. Thus, in the studies using species-specific vocalization in birds (24)(25)(26), mice (27,28), sea lions (29), and monkeys (30)(31)(32)(33)(34)(35), as a rule, a left-hemisphere advantage (25,(27)(28)(29)(30)(31)(32)34), and in few studies a right-hemisphere advantage (26,35), was found-but no asymmetry (24,29,33,35) or a right-hemisphere bias (32,34) when non-species-specific sounds were applied [for review of animal studies, see supporting information (SI) Table S1]. Therefore, some authors concluded that the laterality effect is related to the communicative valence of signals rather than to their acoustic characteristics (36).…”
mentioning
confidence: 99%